2014
DOI: 10.1080/10610278.2014.976221
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid-based squaramides for anion recognition

Abstract: Eight receptors 1 -8 comprising an L-lysine scaffold modified at N-and C-termini with aliphatic alkyl chains and N,N 0 -alkyl amides, respectively, and bearing squaramide moieties on the amino acid side chain were synthesised by a combination of solid-and solution-phase chemistries and shown to complex various anions in 0.5% H 2 O in dimethyl sulfoxide-d 6 solution. All of the receptors were found to bind SO 22 4 ; Cl 2 , AcO 2 and BzO 2 via hydrogen-bond or acid -base interactions with the squaramide protons;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…From our work on squaramides we are familiar with the self-assembly/aggregation of these molecules due to bidirectional H-bonding interactions in addition to π-π stacking brought about by the aromatic cyclobutenedione ring (Elmes et al, 2013, 2014, 2015; Busschaert et al, 2014; Elmes and Jolliffe, 2014; Qin et al, 2016; Marchetti et al, 2018). Moreover, we have also gained considerable experience working with the naphthalimide fluorophore which has fluorescence properties that are highly dependent upon aggregation (Elmes and Gunnlaugsson, 2010; Elmes et al, 2012; Ryan et al, 2012, 2015; Ao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…From our work on squaramides we are familiar with the self-assembly/aggregation of these molecules due to bidirectional H-bonding interactions in addition to π-π stacking brought about by the aromatic cyclobutenedione ring (Elmes et al, 2013, 2014, 2015; Busschaert et al, 2014; Elmes and Jolliffe, 2014; Qin et al, 2016; Marchetti et al, 2018). Moreover, we have also gained considerable experience working with the naphthalimide fluorophore which has fluorescence properties that are highly dependent upon aggregation (Elmes and Gunnlaugsson, 2010; Elmes et al, 2012; Ryan et al, 2012, 2015; Ao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been reported that the pKa's of the hydrogen bonding donor protons affects directly the halide‐binding affinities of anion receptors with an inverse correlation . Furthermore, with a suitable geometry such as the tripodal conjugation, some powerful anion receptors have been developed by these approaches .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we and others have reported that functionalized α–amino acids are a suitable platform for the construction of salt receptors since their framework allows for easy introduction of specific binding domains that might lead to cooperative binding of ion pairs in some cases [33,34,35,36]. Very recently, we have demonstrated that 3-aminobenzoic acid functionalized with arylthiourea and 18-aza-crown-6-ether acting as anion and cation binding units, respectively, also offer a promising platform for obtaining effective ion pair receptors [30,37].…”
Section: Introductionmentioning
confidence: 99%